Optimalisasi Tata Kelola Pupuk Bersubsidi: Strategi Pencegahan Maladministrasi Berbasis Analisis SWOT dan PESTEL - Andi Setyo Pambudi (Universitas Respati Indonesia, 2025)
The distribution of subsidized fertilizer in Indonesia over the past two decades has been marred by various forms of systemic maladministration, including mistargeting, manipulation of beneficiary data, and politicized allocation. This phenomenon reflects structural problems in subsidy governance that have failed to ensure accountability and fairness. This study aims to analyze the main determinants of maladministration in fertilizer subsidy policies and to evaluate the influence of internal institutional factors and external pressures on policy implementation effectiveness. A mixed-method approach was applied, combining a SWOT analysis of the institutional capacity of the Indonesia Ministry of Agriculture, in-depth interviews with 20 key informants from three provinces, and a PESTEL analysis to map external pressures (political, economic, social, technological, environmental, and legal). The findings indicate that maladministration is driven by weak internal governance, limited bureaucratic capacity, and the dominance of local political actors, further exacerbated by unmanaged external pressures. This study recommends governance reform in fertilizer distribution through strengthened data transparency, inter-agency institutional integration, public participation in oversight, and regulatory harmonization at the national level. The study contributes to the development of a more just, responsive, and sustainable subsidy policy framework.